Algorithm for frequency capture and rectification in a low-orbit satellite IoT communication network - Jie Shen (AIMS Press, 2021)
In satellite communication systems, due to relative motion between satellites and that between satellites and the ground, the resulting Doppler frequency offset adversely affects communication synchronization. In this research, Doppler frequency offset compensation and phase offset compensation method eliminate the influence of the Doppler effect on synchronization. The proposed algorithm divides frequency estimate into two steps, coarse and precision. Finally, the corresponding frequency offset and phase offset compensation are performed. The simulation results show that the demodulated output results after frequency offset and phase offset compensation agree well with the original modulation data, indicating that the algorithm is valid and accurate.